Residential inequalities in health-related quality of life among women of reproductive age in four regions of Ethiopia: a decomposition analysis - Tigist Shumet; Nigatu Regassa Geda (BMC, 2023)
Abstract Background Ethiopian rural-urban disparities in key domains of health-related quality of life among women in reproductive age have been huge. However, sources of such inequalities were not studied well. Therefore, this study aimed to assess inequalities in health-related quality of life among women residing in urban and rural areas in four regions of Ethiopia. Methods This study used data extracted from the 2016 Ethiopian Demographic and Health Survey; collected at national level from January 18, 2016, to June 27, 2016. Stratified two stage cluster sampling method were used. The data collected from 2385 women in the age group 15-49 years who were living in four regions (Afar, Benishangul-Gumuz, Gambela, and Somali regions) of Ethiopia were used for this study. The outcome variable, Health-Related Quality of Life (HRQoL), was generated by Principal Component Analysis. Further, Multivariable Ordinary Least Square and Oaxaca decomposition threefold (interaction) were used in the analysis with a p-value less than 0.05 and 95% confidence interval to declare statistical significances. Results Women education, region, religion, wealth index, and husband/partner education were identified as predictors of Health-Related Quality of Life. Women residing in rural areas had far lower health-related quality of life than those living in urban areas. The wealth index and educational level of women were the largest contributor of the inequality in health-related quality of life. Conclusion A substantial inequality in quality of life exist between women who reside in rural and urban areas in those four regions of Ethiopia. The socioeconomic factors more importantly wealth index and educational attainment explained the significant portion of the reported rural-urban disparities. Therefore, Policymakers and local administrators should pay more attention on interventions that promote education and narrowing gap in wealth in rural and urban settings.